Microwave Antennas and Circuits Modeling Using Electromagnetic Field Simulator - Hazdra, Pavel; Polivka, Milan; Sokol, Vratislav (Radioengineering Society, 2005)
Electromagnetic field simulators have become a widely used tool in a design process of microwave circuits and systems. A proper usage of electromagnetic (EM) field simulators allows substantial reduction of the design time providing reliable results. In such case the required parameters of the designed circuit can be reached even at the first manufactured prototype in spite of high complexity of the structure. However, EM simulation as a numerical process suffers from systematic and random errors similar to measurement using real equipment. Thus the setting of the EM-field simulator such as a frequency range, mesh properties, usage of PEC and PMC walls etc. has to be done with the highest attention and the simulation results have to be always verified using well-established techniques. The aim of the paper is to demonstrate the selected capability of EM-field simulators with a few examples of antenna and circuit modeling. Also an issue of reliability and simulation errors will be discussed.
Keywords: CAD; EM-field simulation; microwave modeling; numerical Methods